Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content• The Impact of Public–Private Partnership on the Level of Medical Services Provided: An applied study of Saudi Arabian Airlines General Corporation and Fakeeh Medical GroupCo-Prof. Vivian Mohammed Nasrulddin ,Ms. Amjad Matruh Almutaani ,Ms. Khulud Khalid Baobaid , Ms. Ruba Abdullah Alazwari,Ms. Elaf Mohammed Alotaibi , Ms. Shahad Abdullah Ayn Aldeen• The Impact of Project Management Practices on Institutional Excellence: An Applied Study of the Tarahum Committee for the Care of Prisoners in RiyadhMs. Seham Hamdan Dasan Almakhlafi Alharbi• Comparative Analytical Study of Tax Legislation and its Impact on foreign Direct InvestmentMr. Zain M. AlDahabi , Ms. Fatima A. Algazo ,  Dr. Amal Marshed Alanazi, Ms. Rula Yousef Hajjaj• The Application of the jurisprudential principle "No Harm and Reciprocating Harm" in the Saudi Criminal Procedure LawMs. Shahad Abdulrahman Almazyed• The Nature and Causes of Corruption Crimes and the Importance of International Cooperation in Combating Them: An Analytical Study on the Qatari ExperienceAsst-Prof. Nashat Mfudi Maasfeh• The Impact of Prolonged Conflict on Yemen’s Agricultural Sector: A Longitudinal Analysis of Economic and Labor Dynamics (1961–2021)Mr. Muqbel Ahmed Muqbel Abdullah, Prof. Dr. Sertaç Dokuzlu• Measuring the Alignment Gap Between Organizational Strategic Plans and Vision 2030 Goals: An Analytical Study in Saudi ArabiaMr. Badr Saleh Al-Lehyani, Dr. Alok Tiwari Ramadhar Tiwari
Keywords: Journal of Economic, Administrative and Legal Sciences